ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENAWARAN KOPI ROBUSTA DI KECAMATAN KANDANGAN KABUPATEN TEMANGGUNG - Annisaa' Dyah Suciningtyas; Achma Hendra Setiawan (BISECER (Business Economic Entrepreneurship), 2023)
This study aims to analyze the effect of coffee price, clove price, land area, production costs, and the use of technology on the quantity of Robusta coffee supply from farmers to middlemen in Kandangan District, Temanggung Regency. This study uses a quantitative approach with a population of 1980 coffee farmers. The sample used was 95 people who were divided into the villages of Banjarsari, Ngemplak, Tlogopucang, Blimbing, and Kembangsari with sampling using purposive sampling technique. The data used in the form of primary data based on questionnaires and indept interviews. The research analysis used multiple linear regression (OLS) dummy variables. The results showed that 99.5 percent of Robusta coffee supply in Kandangan District was influenced by price, clove price, land area, production costs and technology dummy variables. The independent variable simultaneously has a positive and significant effect on the supply of robusta coffee in Kandangan District. The variables of price, land area, and production costs have a positive effect, while the price of cloves has a negative effect on the supply of Robusta coffee in Kandangan District. Farmers who use technology have more coffee quantity offered than farmers who do not use technology. However, the price of cloves does not have a significant effect on the supply of robusta coffee because farmers in Kandangan District only produce cloves of 30 kilograms per year on average, while technology also has an insignificant effect due to limited market access.